2016
DOI: 10.1016/j.btre.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic cultivation of Nannochloropsis salina for enhancing biomass and lipid production

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Previous studies highlighted the ability of this alga to metabolize external carbon sources under photosynthetic conditions (mixotrophy) to improve growth 70 72 . We reproduced the reported growth enhancement when cells were shifted from phototrophy (without organic carbon) to a carbon-rich medium 73 , and found that changes in the trophic lifestyle of this alga were also accompanied by substantial physiological and morphological changes (Fig. 7a ).…”
Section: Resultssupporting
confidence: 83%
“…Previous studies highlighted the ability of this alga to metabolize external carbon sources under photosynthetic conditions (mixotrophy) to improve growth 70 72 . We reproduced the reported growth enhancement when cells were shifted from phototrophy (without organic carbon) to a carbon-rich medium 73 , and found that changes in the trophic lifestyle of this alga were also accompanied by substantial physiological and morphological changes (Fig. 7a ).…”
Section: Resultssupporting
confidence: 83%
“…In addition, trials using other media or reinforcing BG11 medium by adding sodium acetate might be advantageous [37,38]. Moreover, addition of carbon-source supplements or sugars created by heterotrophic cultivation [39,40], may also help further in effective production. Use of genetically modified BX1.5 strains may also create an opportunity for increased production potential for the future since genes related to TAG production have been reported [7,31,33,41,42].…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acids EPA and DHA exert a range of biological activities in humans, some overlapping but others distinct for each fatty acid (Calder 2014 ). Fish oil, therefore, remains the main source of marine-derived EPA at present, as EPA-producing algal sources have largely been of photosynthetic origin although attempts have been made to culture some species heterotrophically and optimize conditions to enhance biomass and lipid contents (Marudhupandi et al 2016 ; Ratledge 2005 ). Nevertheless, a Schizochytrium strain/species with a minimum EPA and DHA content of 10 and 22% of total fatty acids, respectively, was reported previously (Gray 2010 ).…”
Section: Introductionmentioning
confidence: 99%